2010
DOI: 10.7310/arfe.46.148
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Productivity and the Constraints on Female Labor Supply in Turkey

Abstract: and the wage rate of hired-in labor. The result obtained is that the hypothesis cannot be supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This is common in other village-level CGE studies such as Dyer et al (2006) and Taylor et al (1999) . 13) In Table 5 of Maru (2010) , the t-test does not reject the null hypothesis of no differences between the marginal productivity of own farm labor and market wages at the 10% level for either male or female members in both irrigated and rain-fed areas. 14) For a male member, a certain rate of machine operating is included in labor employment.…”
Section: How Social Customs Restrict Eu Accession Effects On Female Lmentioning
confidence: 96%
See 2 more Smart Citations
“…This is common in other village-level CGE studies such as Dyer et al (2006) and Taylor et al (1999) . 13) In Table 5 of Maru (2010) , the t-test does not reject the null hypothesis of no differences between the marginal productivity of own farm labor and market wages at the 10% level for either male or female members in both irrigated and rain-fed areas. 14) For a male member, a certain rate of machine operating is included in labor employment.…”
Section: How Social Customs Restrict Eu Accession Effects On Female Lmentioning
confidence: 96%
“…However, as mentioned in Section 2, the numbers of farmers managing animal husbandry and farmers where female members participate in labor were small ; therefore, we needed to adopt other methods. Maru's (2010) survey of Adana Prefecture showed that there were no significant differences between the marginal productivity of own farm labor and market wages for either male or female members. 13) Therefore, the present study assumed that the initial value of the male wage and that of the shadow price of the overall female labor supply were equal to the market wage.…”
Section: ) Basic Settingsmentioning
confidence: 96%
See 1 more Smart Citation